HIV/AIDS, food and nutrition security: impacts and actions [in Arabic] - Gillespie, Stuart; Haddad, Lawrence J.; Jackson, Robin (International Food Policy Research Institute, 2001)
This paper first reviews the potential pathways through which HIV/AIDS affects nutrition, food security, and the livelihoods of households, particularly those dependent on agriculture. With regard to nutrition, HIV/AIDS significantly impacts individuals and households -- through accelerating the vicious circle of inadequate dietary intake and disease, and through diminishing the capacity to ensure the essential food, health and care preconditions of good nutrition. The impacts on agriculture relate to labour and knowledge losses and institutional weakening. The question of how the public sector can and should respond to these challenges is then addressed. The focus is primarily, though not exclusively, on mitigation....Nutritional support has the potential to significantly postpone HIV/AIDS-related illness and prolong life.....Food aid has significant potential for improving the situation of HIV/AIDS-impacted households and communities.